Synthesis of some new S-glycosyl pyrimidine and condensed pyrimidine derivatives - Shehab, Wesam Saber; Mohamed, Enaiat Kamel (European Journal of Chemistry, 2012)
Mercaptopyrimidine (4) was synthesized by the reaction of isothiocyanate and acrylate (1). It was allowed to react with preacetylated sugar bromide and/or halomethylene derivatives to produce alkylated pyrimidines (5,7a-d). Hydrolysis of compound (5) produced compound (6). Interacyclization of compounds (7a-d) afforded thienopyrimidines (8a-d). Moreover oxidation of compound (7b) gave the corresponding thienopyrimidine dioxide (9). Cyanoethylation of compound (4) afforded compound (10) that reacted with hydrazine hydrate to give pyrazolopyrimidine (11). Oxidation of compound 4 afforded bisulphide (12). The cycloaddition product (13) was obtained by reaction of compound 4 with maleic anhydride. Pyrimidopyrimidine, pyrimidopyridazine and tetrazolopyriminde derivatives (16-20) were obtained by reaction of 4-chloropyrimidine (15) with thiourea, benzilhydrazone and sodium azide, respectively. N-alkylated pyrazolopyrimidine (21) was obtained by reaction of compound (15) with acetophenonehydrazone.